1978
DOI: 10.1007/bf00116214
|View full text |Cite
|
Sign up to set email alerts
|

The Fermi surface of platinum

Abstract: We have made measurements of the extremal cross-sectional areas of the open hole surface of the Fermi surface of platinum for the previously unobserved, heavy mass orbits centered on F and X with the magnetic field along the [100] and [110] directions, respectively. When combined with previous measurements, the necessary data associated with all classes of orbits on all three sheets of the surface are now available. Using a relativistic non-muffin-tin, Korringa-Kohn-Rostoker formalism, data were fitted using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

1981
1981
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…Our results are consistent with those from Bordoloi and Auluck [33], Watson-Yang et al [34], and Dye et al [8]. …”
Section: Mass Enhancement Factorsupporting
confidence: 96%
See 1 more Smart Citation
“…Our results are consistent with those from Bordoloi and Auluck [33], Watson-Yang et al [34], and Dye et al [8]. …”
Section: Mass Enhancement Factorsupporting
confidence: 96%
“…We have calculated the band masses for these orbits using Slater Xu-XC and experimental cyclotron masses from Dye et al [8] [34] and Dye et al [8] are also shown for comparison. The calculations of the former have been made on the basis of a first-principles RAPW warped-muffin-tin method, while those of the latter are results of a RKKR fitting scheme.…”
Section: Mass Enhancement Factormentioning
confidence: 99%
“…Using v F = 0.24 × 10 6 m sec −1 for the [111] direction of Pt [24] and v F = 1.4 × 10 6 m sec −1 from the free-electron model for Au, the DMM prediction for is 15.5 MW m −2 K −2 , i.e., G ee 5 GW m −2 K −1 at room temperature. We have previously shown that the Wiedemann-Franz law works well in predicting the thermal conductance of Pd/Ir interfaces [14].…”
Section: Resultsmentioning
confidence: 99%
“…One of these (the 6 band) is broad while the other (XW 5) is substantially narrower, contributing about 80% of the density of states at E F . 35,36 We identify these as the s and d bands, respectively, in our simplified discussion. We expect a similar decomposition of the shift applies to the 8 Li impurity hyperfine coupled to the host conduction bands, but the relative magnitudes of each term will be substantially different than for the host nuclear spins.…”
Section: Resultsmentioning
confidence: 99%
“…This interband coupling must be weak enough that it does not substantially alter the overall band structure that is consistent with low-temperature quantum oscillations. 36 Saturation by this mechanism is reminiscent (perhaps fortuitously) of the Kondo screening of a local magnetic impurity by a degenerate conduction band, where far below the Kondo temperature, the CW-like χ saturates. 46 In this context, consider the effect of the interstitial Li + .…”
Section: Discussionmentioning
confidence: 98%